The apoptotic effect of Zoledronic acid on the nasopharyngeal carcinoma cells via ROS mediated chloride channel activation. (5th July 2018) - Wang, Liang; Gao, Hong; Yang, Xiaoya; Liang, Xiechou; Tan, Qiuchan; Chen, Zhanru; Zhao, Chan; Gu, Zhuoyu; Yu, Meisheng; Zheng, Yanfang; Huang, Yanqing; Zhu, Linyan; et al.
Summary: Zoledronic acid (ZA), a third‐generation bisphosphonate, has been applied for treatment of bone metastases caused by malignant tumors. Recent studies have found its anti‐cancer effects on various tumor cells. One of the mechanisms of anti‐cancer effects of ZA is induction of apoptosis. However, the mechanisms of ZA‐induced apoptosis in tumor cells have not been clarified clearly. In this study, we investigated the roles of chloride channels in ZA‐induced apoptosis in nasopharyngeal carcinoma CNE‐2Z cells. Apoptosis and chloride current were induced by ZA and suppressed by chloride channel blockers. After the knockdown of ClC‐3 expression by ClC‐3 siRNA, ZA‐induced chloride current and apoptosis were significantly suppressed, indicating that the chloride channel participated in ZA‐induced apoptosis may be ClC‐3. When reactive oxygen species (ROS) generation was inhibited by the antioxidant N‐acetyl‐L‐cysteine (L‐NAC), ZA‐induced apoptosis and chloride current were blocked accordingly, suggesting that ZA induces apoptosis through promoting ROS production and subsequently activating chloride channel.